2014
DOI: 10.5194/acpd-14-26349-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying fire plumes in the Arctic with tropospheric FTIR measurements and transport models

Abstract: We investigate Arctic tropospheric composition using ground-based Fourier transform infrared (FTIR) solar absorption spectra, recorded at the Polar Environment Atmospheric Research Laboratory (PEARL, Eureka, Nunavut, Canada, 80 • 05 N, 86 • 42 W) and at Thule (Greenland, 76 • 53 N, −68 • 74 W) from 2008 to 2012. The target species, carbon monoxide (CO), hydrogen cyanide (HCN), ethane (C 2 H 6 ), acetylene (C 2 H 2 ), formic acid (HCOOH), and formaldehyde (H 2 CO) are emitted by biomass burning and can be trans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 80 publications
5
15
2
Order By: Relevance
“…Large variability of HCN is observed in the summer months at Eureka corresponding to the boreal fire season from May to August [ Macias Fauria and Johnson , ]. Particularly, large fire events in Russia during July 2008 and August 2010 are observed in the time series [ Viatte et al , , ] in addition to the 2014 Northwest Territories fires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large variability of HCN is observed in the summer months at Eureka corresponding to the boreal fire season from May to August [ Macias Fauria and Johnson , ]. Particularly, large fire events in Russia during July 2008 and August 2010 are observed in the time series [ Viatte et al , , ] in addition to the 2014 Northwest Territories fires.…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently shown that solar absorption spectroscopy using FTIR spectrometers can be used to measure NH 3 total columns [ Dammers et al , ], while biomass burning emissions of carbon monoxide (CO), hydrogen cyanide (HCN) and ethane (C 2 H 6 ) have been previously measured in the Canadian Arctic at Eureka [ Viatte et al , , , ], Australia [ Paton‐Walsh et al , , ], Reunion Island [ Vigouroux et al , ], and Japan [ Zhao et al , ]. The ground‐based FTIR instrument at Eureka provides measurements of NH 3 where satellite observations and in situ data are sparse or nonexistent.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2015 smoke from peat fires in Indonesia blanketed much of Asia in a persistent plume of pollution throughout September and October (Field et al, ; Huijnen et al, ), contributing to an estimated 100,000 premature deaths due to exposure to fire‐related air pollution (Koplitz et al, ). Due to long‐range transport of these emissions, tropical peatland fires frequently affect large areas of the world (Andreae, ; Edwards et al, ; Viatte et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For CO, HCN, and C 2 H 6 , enhanced total columns are periodically observed in May to September at Eureka and Thule, corresponding to the boreal wildfire season (Macias Fauria & Johnson, ). While enhancements of CO, HCN, and C 2 H 6 due to wildfire emissions are observed annually (Viatte et al, ), the only clear case of NH 3 wildfire emissions in the past was observed in July to August 2014 from the NWT wildfires (Lutsch et al, ). However, this does not take into account possible missed events due to instrument downtime or nonclear sky conditions preventing measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Solar-absorption spectra were processed using the SFIT4 retrieval algorithm (https://wiki.ucar.edu/display/ sfit4/) based on the optimal estimation method (Rodgers & Connor, 2003). Retrievals of CO, HCN, and C 2 H 6 at Eureka and Thule are performed following NDACC Infrared Working Group (IRWG) recommendations as described in Viatte et al (2013Viatte et al ( , 2014Viatte et al ( , 2015 and Lutsch et al (2016) and references therein. For both sites, retrievals of NH 3 were performed following the procedure of Lutsch et al (2016) based on the method of Dammers et al (2015).…”
Section: Ftir Retrievalsmentioning
confidence: 99%